The Role of Estrogen Signaling and Exercise in Drug Abuse: A Review - Rania Ahmed; Samuel Zyla; Nikki Hammond; Kenneth Blum; Panayotis K. Thanos (Clinics and Practice, 2024)
Background: Discovering how sex differences impact the efficacy of exercise regimens used for treating drug addiction is becoming increasingly important. Estrogen is a hormone believed to explain a large portion of sex differences observed during drug addiction, and why certain exercise regimens are not equally effective between sexes in treatment. Addiction is currently a global hindrance to millions, many of whom are suffering under the influence of their brain’s intrinsic reward system coupled with external environmental factors. Substance abuse disorders in the U.S. alone cost billions of dollars annually. Review Summary: Studies involving the manipulation of estrogen levels in female rodents, primarily via ovariectomy, highlight its impact regarding drug addiction. More specifically, female rodents with higher estrogen levels during the estrus phase increase cocaine consumption, whereas those in the non-estrus phase (low estrogen levels) decrease cocaine consumption. If estrogen is reintroduced, self-administration increases once again. Exercise has been proven to decrease relapse tendency, but its effect on estrogen levels is not fully understood. Conclusions: Such findings and results discussed in this review suggest that estrogen influences the susceptibility of females to relapse. Therefore, to improve drug-abuse-related treatment, exercise regimens for females should be generated based on key sex differences with respect to males.